Public awareness toward Bancassurance in Malaysia / Maizatul Huda Mohammad Zulkifli Hashim - Mohammad Zulkifli Hashim, Maizatul Huda (Faculty of Business and Management, 2010)
Bancassurance is one of the well-growth finance and insurance industry nowadays. Many efforts have been done by most of Bancassurance Company in order to educate the Malaysian what is all about the Bancassurance. However the awareness and knowledge among Malaysia citizen is being doubted. This research is trying to determine awareness level of Malaysian citizen towards Bancassurance in Malaysia. This research also discuss on history of Bancassurance in Malaysia, the Bancassurance concepts, and advantages and disadvantages of Bancassurance. In order to achieve the objectives, 100 respondents have been selected randomly to answer the questionnaire. The result revealed that the public awareness toward Bancassurance still low.